Immobilization of modular peptides on graphene cocktail for differentiation of human mesenchymal stem cells to hepatic-like cells - Adibi-Motlagh, Behzad; Hashemi, Ehsan; Akhavan, Omid; Khezri, Jafar; Rezaei, Aram; Zamani Amir Zakria, Javad; Siadat, Seyed Davar; Sahebghadam Lotfi, Abbas; Farmany, Abbas (Frontiers in Chemistry, 2022)
In this study, two novel biomimetic modular peptide motifs based on the alpha-2 subunit of type IV collagen (CO4A2) were designed and immobilized on a graphene platform to imitate integrin and heparan sulfate- (HS-) binding proteins. The in silico study was used to design 9-mer K[KGDRGD]AG and 10-mer KK[SGDRGD]AG for testing designed Integrin-Binding Peptide (dIBP) and HS-Binding Peptide (dHBP). The virtual docking technique was used to optimize the peptide motifs and their relevant receptors. Molecular dynamic (MD) simulation was used to evaluate the stability of peptide-receptor complexes. The effect of the platform on the differentiation of human mesenchymal stem cells (hMSCs) to hepatic-like cells (HLCs) was evaluated. After differentiation, some hepatic cells’ molecular markers such as albumin, AFP, CK-18, and CK-19 were successfully followed. Graphene-heparan sulfate binding peptide (G-HSBP) enhances the mature hepatic markers’ expression instead of control (p ≤ 0.05). The pathological study showed that the designed platform is safe, and no adverse effects were seen till 21 days after implantation.